Solid waste-based road material as well as preparation method and application thereof
By using drilling rock chips, coal gangue and aluminum ore mud in solid waste subway materials, and combining magnetic field heat treatment technology, the problem of poor pavement repair performance in cold areas has been solved, and the low-temperature hardening performance of the material is improved and the effect of rapid pavement repair is achieved.
Patent Information
- Application Number
- CN202411645774.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing solid waste subway materials are poorly constructed and performed in extremely cold areas, resulting in difficult repair of road surfaces in cold areas such as northern and high-altitude mountainous areas and poor mechanical performance.
Drilling rock chips, coal gangue and aluminum ore sludge are used as solid waste base system, supplemented by alkaline exciters, water reducing agents and early strength agents, and medium- and low-temperature activation is carried out through magnetic field heat treatment technology to improve the low-temperature hardening performance of the material.
It significantly improves the low-temperature hardening performance of solid waste subway materials, reduces the constraints of ambient temperature on concrete pavement construction, and can achieve rapid and efficient repair of pavement in a low temperature environment of -25℃.
Smart Images

Figure CN119551940A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of roadbed materials, and in particular to a solid waste-based road material and a preparation method and application thereof. Background Art
[0002] With the acceleration of the global industrialization process, the emission of various types of industrial solid waste (solid waste) has increased dramatically, bringing tremendous pressure to the environment. Especially in today's increasingly scarce resources, how to effectively treat and utilize these solid wastes and realize the recycling of resources has become a hot issue of global concern. In the field of road construction, traditional roadbed materials such as natural sand and gravel, cement, etc. are not only limited in resources, but also cause damage to the environment during mining and processing, and their costs are also rising. Therefore, finding new environmentally friendly materials to replace traditional roadbed materials, especially using solid waste to prepare road materials, has become an important research direction in the field of road engineering.
[0003] In recent years, although some studies have attempted to convert industrial waste into roadbed materials, these solid waste-based road materials still face many challenges in practical applications, especially in some special environmental conditions, such as extremely cold regions. For example, in cold areas such as northern my country and high-altitude mountainous areas, the low temperature environment places extremely stringent requirements on the construction and performance of pavement materials. Existing solid waste-based road materials often have problems such as poor raw material adaptability and low activity, which leads to great construction difficulties and poor mechanical properties, making it difficult to meet the urgent needs of rapid road repair in cold regions. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a solid waste-based road material and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a solid waste-based road material, which comprises the following components in parts by weight:
[0006] 40-55 parts of drilling cuttings, 20-30 parts of coal gangue, 20-30 parts of aluminum ore mud, 15-25 parts of alkaline activator, 0.2-0.5 parts of water reducer, 0.3-0.8 parts of early strength agent and 10-15 parts of water.
[0007] Furthermore, the weight ratio of the drilling cuttings, the coal gangue and the aluminum ore mud is 2:1:1.
[0008] Furthermore, the solid waste-based road material comprises the following components in parts by weight:
[0009] 48 parts of drilling cuttings, 24 parts of coal gangue, 24 parts of aluminum ore mud, 21 parts of alkaline activator, 0.3 parts of water reducer, 0.5 parts of early strength agent and 13 parts of water.
[0010] Furthermore, the alkaline activator includes at least one of sodium hydroxide, potassium hydroxide and potassium water glass; the water reducer includes at least one of aminosulfonate water reducer and polycarboxylic acid water reducer; and the early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of (1-3):(1-2).
[0011] Furthermore, the construction and maintenance temperature of the solid waste-based road material is -25°C.
[0012] In a second aspect, the present invention provides a method for preparing the solid waste-based road material according to any one of the first aspects, the preparation method comprising the following steps:
[0013] The drilling cuttings, coal gangue and aluminum ore mud are stirred and mixed to obtain a first mixed material;
[0014] The first mixed material is subjected to magnetic field heat treatment, and then crushed and sieved to obtain a second mixed material;
[0015] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0016] Furthermore, the magnetic field heat treatment step includes the following process:
[0017] The first mixed material is placed in a magnetic field sintering furnace, and first subjected to heat preservation treatment at a flux coil current of 3 to 7A and a temperature of 300 to 400°C for 0.5 to 1 hour, then subjected to heat preservation treatment at a current of 15 to 20A and a temperature of 700 to 800°C for 1 to 2 hours, and finally cooled with the furnace.
[0018] Furthermore, in terms of weight percentage, the particle size grading of the second mixture is: 4-8% of the particles have a particle size of less than 0.075 mm, 10-15% of the particles have a particle size of 0.075 mm to 1.25 mm, 65-75% of the particles have a particle size of 1.5 mm to 2.5 mm, and the remaining particle size of the second mixture is 2.5 mm to 5.0 mm.
[0019] In a third aspect, the present invention provides the use of the solid waste-based road material described in any one of the first aspect and the second aspect in repairing pavement in cold regions.
[0020] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0021] An embodiment of the present invention provides a method for preparing solid waste-based road materials. The present invention adopts drilling cuttings, coal gangue and aluminum ore mud in appropriate proportions as the solid waste base material system, supplemented with reasonable additives, and combines magnetic field heat treatment technology for medium and low temperature activation, which significantly improves the low-temperature hardening performance of the obtained solid waste-based road materials and reduces the constraints of ambient temperature on concrete pavement construction, especially in extremely cold areas, such as when dealing with a low temperature environment of -25°C, it can achieve rapid and efficient repair of the road surface, meeting the use requirements of pavement material performance in cold areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 A schematic flow chart of a method for preparing a solid waste-based road material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0027] In a first aspect, the present invention provides a solid waste-based road material, which comprises the following components in parts by weight:
[0028] 40-55 parts of drilling cuttings, 20-30 parts of coal gangue, 20-30 parts of aluminum ore mud, 15-25 parts of alkaline activator, 0.2-0.5 parts of water reducer, 0.3-0.8 parts of early strength agent and 10-15 parts of water.
[0029] An embodiment of the present invention provides a solid waste-based road material. The present invention adopts drilling cuttings, coal gangue and aluminum ore mud in appropriate proportions as the solid waste base material system, supplemented with reasonable additives, and combines magnetic field heat treatment technology for medium and low temperature activation, which significantly improves the low-temperature hardening performance of the obtained solid waste-based road material and reduces the constraints of ambient temperature on concrete pavement construction, especially in extremely cold areas, such as when dealing with a low temperature environment of -25°C, it can achieve rapid and efficient repair of the road surface, meeting the use requirements of pavement material performance in cold areas.
[0030] In the present invention, drilling cuttings are water-based drilling cuttings produced by drilling waste generated by preparing drilling mud for oil production with water as the continuous phase and solidified, and the waste code of the drilling cuttings is 071-001-S12 in the "Solid Waste Classification and Code Catalog". In some specific embodiments, the oxides in the water-based drilling cuttings used mainly include, by weight percentage: SiO2 content of 41.6-50.2%, Al2O3 content of 7.0-9.3%, and Fe2O3 content of 3.9-5.7%.
[0031] In the present invention, aluminum ore mud, or bauxite washing mud, is the mud produced in the process of bauxite washing, and its waste code is 091-007-S05 in the "Solid Waste Classification and Code Catalog". In some specific embodiments, the oxides in the aluminum ore mud used mainly include: SiO2 content of 23.4-26.8wt%, Al2O3 content of 40.1-45.7wt%.
[0032] In the present invention, coal gangue is a black-gray rock solid waste discharged from coal mines during the production processes of development and excavation, coal mining and coal washing, and its waste code is 060-001-S04 in the "Solid Waste Classification and Code Catalog". In some specific embodiments, the oxides in the coal gangue used mainly include, by weight percentage: SiO2 content is 58.3-62.0%, Al2O3 content is 21.7-25.9%, and Fe2O3 content is 4.1-5.5%.
[0033] In some specific embodiments, the weight ratio of the drilling cuttings, the coal gangue and the aluminum ore mud is 2:1:1.
[0034] In some specific embodiments, the solid waste-based road material includes the following components in parts by weight:
[0035] 48 parts of drilling cuttings, 24 parts of coal gangue, 24 parts of aluminum ore mud, 21 parts of alkaline activator, 0.3 parts of water reducer, 0.5 parts of early strength agent and 13 parts of water.
[0036] In some specific embodiments, the alkaline activator includes at least one of sodium hydroxide, potassium hydroxide and potassium water glass, preferably potassium hydroxide and potassium water glass with a modulus of 2.6-3.0 in a weight ratio of 1:1, and the potassium water glass can be prepared by itself according to the preparation process disclosed in the prior art or directly adopt commercially available potassium water glass such as product models ZFK27-49A and ZFK29-44A of Foshan Zhongfa Water Glass Factory; the water reducer includes at least one of aminosulfonate water reducer and polycarboxylic acid water reducer, preferably polycarboxylic acid water reducer, and specifically commercially available polycarboxylic acid water reducer such as Jinan Quanchi New Materials Co., Ltd., Shandong Hongquan Chemical Technology Co., Ltd. and other companies can be adopted; the early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of (1-3): (1-2).
[0037] In some specific embodiments, the construction and maintenance temperature of the solid waste-based road material is -25°C.
[0038] In a second aspect, based on the same inventive concept, the present invention provides a method for preparing the solid waste-based road material as described in any one of the first aspects, such as Figure 1 As shown, the preparation method comprises the following steps:
[0039] The drilling cuttings, coal gangue and aluminum ore mud are stirred and mixed to obtain a first mixed material;
[0040] The first mixed material is subjected to magnetic field heat treatment, and then crushed and sieved to obtain a second mixed material;
[0041] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0042] Compared with traditional high-temperature sintering activation (temperature>1000°C), the present invention uses magnetic field heat treatment technology to activate solid waste base materials at medium and low temperatures, with better activation effect and lower energy consumption.
[0043] In some specific embodiments, the magnetic field heat treatment step includes the following process:
[0044] The first mixed material is placed in a magnetic field sintering furnace, and first subjected to heat preservation treatment at a flux coil current of 3 to 7A and a temperature of 300 to 400°C for 0.5 to 1 hour, then subjected to heat preservation treatment at a current of 15 to 20A and a temperature of 700 to 800°C for 1 to 2 hours, and finally cooled with the furnace.
[0045] In some specific embodiments, the particle size grading of the second mixture is, in percentage by weight: 4-8% of particles have a particle size of less than 0.075 mm, 10-15% of particles have a particle size of 0.075 mm to 1.25 mm, 65-75% of particles have a particle size of 1.5 mm to 2.5 mm, and the remaining particle size of the second mixture is 2.5 mm to 5.0 mm.
[0046] In a third aspect, based on the same inventive concept, the present invention provides the use of the solid waste-based road material described in any one of the first aspect and the second aspect in repairing pavement in cold regions.
[0047] It should be noted that, unless otherwise specified or described, the components and raw materials involved in the solid waste-based road material and the preparation method thereof provided in the embodiments of the present invention can be directly commercially available products. At the same time, unless otherwise specified or described, the steps involved in the preparation method can be carried out according to the steps and parameters disclosed in the prior art or using existing equipment, and the present invention document will not repeat them one by one.
[0048] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0049] Example 1
[0050] This example provides a solid waste-based road material, which includes the following components in parts by weight:
[0051] 48 parts of drilling cuttings, 24 parts of coal gangue, 24 parts of aluminum ore mud, 21 parts of alkaline activator, 0.3 parts of water reducer, 0.5 parts of early strength agent and 13 parts of water;
[0052] The alkaline activator is composed of potassium hydroxide and potassium water glass with a modulus of 2.6-2.8 in a weight ratio of 1:1;
[0053] The water reducer is a polycarboxylate water reducer;
[0054] The early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of 2:1.5.
[0055] The method for preparing the above-mentioned solid waste-based road material comprises the following steps:
[0056] Step (1): stirring and mixing drilling cuttings, coal gangue and aluminum ore mud to obtain a first mixture;
[0057] Step (2): placing the first mixture obtained in step (1) in a magnetic field sintering furnace for magnetic field heat treatment, firstly, carrying out heat preservation treatment under the conditions of a magnetic flux coil current of 5A and a temperature of 360°C for 1 hour, then carrying out heat preservation treatment under the conditions of 18A and a temperature of 740°C for 1.5 hours, and finally cooling with the furnace; crushing and screening the first mixture after the magnetic field heat treatment to obtain a second mixture; wherein, in terms of weight percentage, the particle size gradation of the second mixture is: the proportion of particles with a particle size of less than 0.075 mm is 5%, the proportion of particles with a particle size of 0.075 mm to 1.25 mm is 12%, the proportion of particles with a particle size of 1.5 mm to 2.5 mm is 70%, and the proportion of particles with a particle size of 2.5 mm to 5.0 mm is 13%;
[0058] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0059] The solid waste-based road material in this example was cured at -25°C and then subjected to a mechanical property test. The test results are shown in Table 1.
[0060] Example 2
[0061] This example provides a solid waste-based road material, which includes the following components by weight:
[0062] 40 parts of drilling cuttings, 30 parts of coal gangue, 30 parts of aluminum ore mud, 15 parts of alkaline activator, 0.2 parts of water reducer, 0.3 parts of early strength agent and 10 parts of water;
[0063] The alkaline activator is composed of potassium hydroxide and potassium water glass with a modulus of 2.6-2.8 in a weight ratio of 1:1;
[0064] The water reducer is a polycarboxylate water reducer;
[0065] The early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of 1:2.
[0066] The method for preparing the above-mentioned solid waste-based road material comprises the following steps:
[0067] Step (1): stirring and mixing drilling cuttings, coal gangue and aluminum ore mud to obtain a first mixture;
[0068] Step (2): placing the first mixture obtained in step (1) in a magnetic field sintering furnace for magnetic field heat treatment, firstly carrying out heat preservation treatment at a magnetic flux coil current of 3A and a temperature of 400°C for 0.5 hour, then carrying out heat preservation treatment at a current of 20A and a temperature of 700°C for 2 hours, and finally cooling with the furnace; crushing and screening the first mixture after the magnetic field heat treatment to obtain a second mixture; wherein, in terms of weight percentage, the particle size gradation of the second mixture is: the proportion of particles with a particle size of less than 0.075 mm is 8%, the proportion of particles with a particle size of 0.075 mm to 1.25 mm is 15%, the proportion of particles with a particle size of 1.5 mm to 2.5 mm is 65%, and the proportion of particles with a particle size of 2.5 mm to 5.0 mm is 12%;
[0069] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0070] The solid waste-based road material in this example was cured at -25°C and then subjected to a mechanical property test. The test results are shown in Table 1.
[0071] Example 3
[0072] This example provides a solid waste-based road material, which includes the following components in parts by weight:
[0073] 55 parts of drilling cuttings, 20 parts of coal gangue, 20 parts of aluminum ore mud, 25 parts of alkaline activator, 0.5 parts of water reducer, 0.8 parts of early strength agent and 15 parts of water;
[0074] The alkaline activator is composed of potassium hydroxide and potassium water glass with a modulus of 2.6-2.8 in a weight ratio of 1:1;
[0075] The water reducer is a polycarboxylate water reducer;
[0076] The early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of 3:1.
[0077] The method for preparing the above-mentioned solid waste-based road material comprises the following steps:
[0078] Step (1): stirring and mixing drilling cuttings, coal gangue and aluminum ore mud to obtain a first mixture;
[0079] Step (2): placing the first mixture obtained in step (1) in a magnetic field sintering furnace for magnetic field heat treatment, firstly carrying out heat preservation treatment under the conditions of a magnetic flux coil current of 7A and a temperature of 300°C for 1 hour, then carrying out heat preservation treatment under the conditions of 15A and a temperature of 800°C for 2 hours, and finally cooling with the furnace; crushing and screening the first mixture after the magnetic field heat treatment to obtain a second mixture; wherein, in terms of weight percentage, the particle size gradation of the second mixture is: the proportion of particles with a particle size of less than 0.075 mm is 4%, the proportion of particles with a particle size of 0.075 mm to 1.25 mm is 10%, the proportion of particles with a particle size of 1.5 mm to 2.5 mm is 75%, and the proportion of particles with a particle size of 2.5 mm to 5.0 mm is 11%;
[0080] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0081] The solid waste-based road material in this example was cured at -25°C and then subjected to a mechanical property test. The test results are shown in Table 1.
[0082] Comparative Example 1
[0083] This example provides a solid waste-based road material and a preparation method thereof, which differs from Example 1 only in that the amount of drilling cuttings is adjusted to 24 parts and the amount of aluminum ore mud is adjusted to 48 parts; the remaining steps and parameters are the same.
[0084] This example provides a solid waste-based road material, which includes the following components by weight:
[0085] 24 parts of drilling cuttings, 24 parts of coal gangue, 48 parts of aluminum ore mud, 21 parts of alkaline activator, 0.3 parts of water reducer, 0.5 parts of early strength agent and 13 parts of water;
[0086] The alkaline activator is composed of potassium hydroxide and potassium water glass with a modulus of 2.6-2.8 in a weight ratio of 1:1;
[0087] The water reducer is a polycarboxylate water reducer;
[0088] The early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of 2:1.5.
[0089] The method for preparing the above-mentioned solid waste-based road material comprises the following steps:
[0090] Step (1): stirring and mixing drilling cuttings, coal gangue and aluminum ore mud to obtain a first mixture;
[0091] Step (2): placing the first mixture obtained in step (1) in a magnetic field sintering furnace for magnetic field heat treatment, firstly, carrying out heat preservation treatment under the conditions of a magnetic flux coil current of 5A and a temperature of 360°C for 1 hour, then carrying out heat preservation treatment under the conditions of 18A and a temperature of 740°C for 1.5 hours, and finally cooling with the furnace; crushing and screening the first mixture after the magnetic field heat treatment to obtain a second mixture; wherein, in terms of weight percentage, the particle size gradation of the second mixture is: the proportion of particles with a particle size of less than 0.075 mm is 5%, the proportion of particles with a particle size of 0.075 mm to 1.25 mm is 12%, the proportion of particles with a particle size of 1.5 mm to 2.5 mm is 70%, and the proportion of particles with a particle size of 2.5 mm to 5.0 mm is 13%;
[0092] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0093] The solid waste-based road material in this example was cured at -25°C and then subjected to a mechanical property test. The test results are shown in Table 1.
[0094] Comparative Example 2
[0095] This example provides a solid waste-based road material and a preparation method thereof, which is different from Example 1 only in that the magnetic field heat treatment in step (2) is adjusted to conventional heat treatment; the remaining steps and parameters are the same.
[0096] This example provides a solid waste-based road material, which includes the following components by weight:
[0097] 48 parts of drilling cuttings, 24 parts of coal gangue, 24 parts of aluminum ore mud, 21 parts of alkaline activator, 0.3 parts of water reducer, 0.5 parts of early strength agent and 13 parts of water;
[0098] The alkaline activator is composed of potassium hydroxide and potassium water glass with a modulus of 2.6-2.8 in a weight ratio of 1:1;
[0099] The water reducer is a polycarboxylate water reducer;
[0100] The early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of 2:1.5.
[0101] The method for preparing the above-mentioned solid waste-based road material comprises the following steps:
[0102] Step (1): stirring and mixing drilling cuttings, coal gangue and aluminum ore mud to obtain a first mixture;
[0103] Step (2): placing the first mixed material obtained in step (1) in a sintering furnace for heat treatment, firstly carrying out heat preservation treatment at a temperature of 360° C. for 1 hour, then carrying out heat preservation treatment at a temperature of 740° C. for 1.5 hours, and finally cooling with the furnace; crushing and screening the heat-treated first mixed material to obtain a second mixed material; wherein, in terms of weight percentage, the particle size distribution of the second mixed material is as follows: the particle size <0.075 mm accounts for 5%, the particle size of 0.075 mm to 1.25 mm accounts for 12%, the particle size of 1.5 mm to 2.5 mm accounts for 70%, and the particle size of 2.5 mm to 5.0 mm accounts for 13%;
[0104] The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
[0105] The solid waste-based road material in this example was cured at -25°C and then subjected to a mechanical property test. The test results are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] It can be seen from Table 1 that, compared with the comparative example, under the low temperature construction and maintenance conditions of -25°C, the solid waste-based road material provided by the embodiment of the present invention has higher early strength, has the characteristics of fast hardening and early strength, and can meet the use requirements of pavement material performance in cold areas.
[0110] In summary, the embodiments of the present invention provide a solid waste-based road material and a preparation method and application thereof. The present invention adopts drilling cuttings, coal gangue and aluminum ore mud in appropriate proportions as the solid waste base material system, supplemented with reasonable additives, and combines magnetic field heat treatment technology for medium and low temperature activation, which significantly improves the low-temperature hardening performance of the obtained solid waste-based road material and reduces the constraints of ambient temperature on concrete pavement construction, especially in extremely cold areas, such as when dealing with a low temperature environment of -25°C, it can achieve rapid and efficient repair of the road surface, meeting the use requirements of pavement material performance in cold areas.
[0111] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0112] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A solid waste-based road material, characterized in that: The solid waste-based road material comprises the following components in parts by weight: 40-55 parts of drilling cuttings, 20-30 parts of coal gangue, 20-30 parts of aluminum ore mud, 15-25 parts of alkaline activator, 0.2-0.5 parts of water reducer, 0.3-0.8 parts of early strength agent and 10-15 parts of water.
2. The solid waste-based road material according to claim 1, characterized in that: The weight ratio of the drilling cuttings, the coal gangue and the aluminum ore mud is 2:1:
1.
3. The solid waste-based road material according to claim 1, characterized in that: The solid waste-based road material comprises the following components in parts by weight: 48 parts of drilling cuttings, 24 parts of coal gangue, 24 parts of aluminum ore mud, 21 parts of alkaline activator, 0.3 parts of water reducer, 0.5 parts of early strength agent and 13 parts of water.
4. The solid waste-based road material according to claim 1, characterized in that: The alkaline activator includes at least one of sodium hydroxide, potassium hydroxide and potassium water glass; the water reducer includes at least one of aminosulfonate water reducer and polycarboxylic acid water reducer; the early strength agent is composed of calcium nitrate and sodium sulfate in a weight ratio of (1-3): (1-2).
5. The solid waste-based road material according to claim 1, characterized in that: The construction and maintenance temperature of the solid waste-based road material is -25°C.
6. A method for preparing a solid waste-based road material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The drilling cuttings, coal gangue and aluminum ore mud are stirred and mixed to obtain a first mixed material; The first mixed material is subjected to magnetic field heat treatment, and then crushed and sieved to obtain a second mixed material; The second mixed material and the remaining components in the solid waste-based road material are stirred and mixed to obtain the solid waste-based road material.
7. The method for preparing solid waste-based road materials according to claim 6, characterized in that: The magnetic field heat treatment step includes the following processes: The first mixed material is placed in a magnetic field sintering furnace, and first subjected to heat preservation treatment at a flux coil current of 3 to 7A and a temperature of 300 to 400°C for 0.5 to 1 hour, then subjected to heat preservation treatment at a current of 15 to 20A and a temperature of 700 to 800°C for 1 to 2 hours, and finally cooled with the furnace.
8. The method for preparing solid waste-based road materials according to claim 6, characterized in that: In terms of weight percentage, the particle size gradation of the second mixture is: the particle size <0.075mm accounts for 4-8%, the particle size of 0.075mm-1.25mm accounts for 10-15%, the particle size of 1.5mm-2.5mm accounts for 65-75%, and the remaining particle size of the second mixture is 2.5mm-5.0mm.
9. Use of the solid waste-based road material according to any one of claims 1 to 5 in repairing pavement in cold regions.
Citation Information
Patent Citations
Oil-base rock debris cement paste and preparation method thereof
CN109626883A
An application method of treated oil-based rock debris in an inorganic stable road base
CN109853312A
Environment-friendly coal gangue-based all-solid waste pavement base mixture and preparation method thereof
CN116354655A
Composition for pavement crack grouting repair, pavement crack grouting repair material and preparation method of pavement crack grouting repair material
CN116477883A
Coal gangue roadbed material and preparation method thereof
CN116854411A